BEYOND RELIGIOUS BOUNDARIES: EXPRESSING THE ATTRACTION OF HALAL PRODUCTS FOR NON-MUSLIM - Atieqoh, Siti; Kustini, Kustini; Warnis, Warnis (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
This study explores the shifting meaning of halal products beyond their religious dimension, highlighting their growing appeal to non-Muslim consumers in Indonesia and other Asian nations, including Japan and South Korea. Halal is no longer perceived solely as a marker of Islamic religiosity but increasingly as a symbol of quality assurance, hygiene, and food safety. Through a qualitative approach, complemented by literature review, surveys, and case studies, the results indicate reveal that non-Muslim consumers associate halal with strict production standards, transparency in supply chains, and assurance of safe ingredients. The segmentation of non-Muslim consumers shows diverse motivations, including quality, health consciousness, lifestyle trends, solidarity, and accessibility. Empirical data and global reports demonstrate that halal is now positioned alongside international labels such as organic, eco-friendly, and non-GMO, making it a universal value proposition. However, challenges remain, such as the perception of halal as an exclusive religious label, limited consumer literacy, and the high cost of certification. This study concludes that halal has the potential to serve as both an inclusive market strategy and a form of cross-cultural economic diplomacy, bridging religious boundaries while reinforcing consumer trust in the global market.